2021
DOI: 10.1101/2021.02.10.430499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bifurcated monocyte states are predictive of mortality in severe COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 infection presents with varied clinical manifestations, ranging from mild symptoms to acute respiratory distress syndrome (ARDS) with high mortality. Despite extensive analyses, there remains an urgent need to delineate immune cell states that contribute to mortality in severe COVID-19. We performed high-dimensional cellular and molecular profiling of blood and respiratory samples from critically ill COVID-19 patients to define immune cell genomic states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…The longitudinal measurements in acute COVID-19 patients showed that the progressive increase of HLA-DR expression in monocytes paralleled an increasing specific T cell response, and this was mostly observed in patients who survived, whereas patients who failed to augment HLA-DR expression in monocytes also failed to mount protective anti-SARS-CoV-2 cellular immune responses and died. These results agree with previous data which suggested a mortality predictive value of dual monocyte state and gene modules in severe COVID-19 [ 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…The longitudinal measurements in acute COVID-19 patients showed that the progressive increase of HLA-DR expression in monocytes paralleled an increasing specific T cell response, and this was mostly observed in patients who survived, whereas patients who failed to augment HLA-DR expression in monocytes also failed to mount protective anti-SARS-CoV-2 cellular immune responses and died. These results agree with previous data which suggested a mortality predictive value of dual monocyte state and gene modules in severe COVID-19 [ 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the ability of our model to recapitulate severe disease by, in part, regulating monocyte differentiation raises the possibility that patients with low monocyte levels [7] may benefit from treatments that better regulate monocyte differentiation. This is in line with recent studies identifying distinct transcriptional factors as regulators of differentiated monocyte fates in inflammatory conditions [74,75], and clinical observations that monocyte dysregulation is present in severe COVID-19 [76,77]. It also raises the possibility that modulation by exogenous cytokines, including macrophage colony-stimulating factor in combination with IL-4 and tumour necrosis factor-alpha (TNF-α), may be able to direct monocyte differentiation in favour of monocyte-derived dendritic cells and reduce this response [74].…”
Section: Plos Pathogenssupporting
confidence: 90%
“…3 A – C). However, other reports have noted the higher incidence of inflammatory monocytes in COVID-19 [ 60 , 61 ] and other viral illnesses [62] . A recent report noted neutrophilia in only 31% of patients with severe COVID-19 [63] .…”
Section: Discussionmentioning
confidence: 87%